Soft Ionics: Governing Physics and State of Technologies - Tepermeister, Max; Bosnjak, Nikola; Dai, Jinyue; Zhang, Xinyue; Kielar, Samuel M.; Wang, Zhongtong; Tian, Zhiting; Suntivich, Jin; Silberstein, Meredith N. (Frontiers in Physics, 2022)
Soft ionic materials combine charged mobile species and tailored polymer structures in a manner that enables a wide array of functional devices. Traditional metal and silicon electronics are limited to two charge carriers: electrons and holes. Ionic devices hold the promise of using the wide range of chemical and molecular properties of mobile ions and polymer functional groups to enable flexible conductors, chemically specific sensors, bio-compatible interfaces, and deformable digital or analog signal processors. Stand alone ionic devices would need to have five key capabilities: signal transmission, energy conversion/harvesting, sensing, actuation, and signal processing. With the great promise of ionically-conducting materials and ionic devices, there are several fields working independently on pieces of the puzzle. These fields range from waste-water treatment research to soft robotics and bio-interface research. In this review, we first present the underlying physical principles that govern the behavior of soft ionic materials and devices. We then discuss the progress that has been made on each of the potential device components, bringing together finding from a range of research fields, and conclude with discussion of opportunities for future research.